Analysis Of 3D Gantry Crane System By PID And VSC For Positioning Trolley And Oscillation Reduction - Rozaimi, Ghazali (Universiti Teknikal Malaysia Melaka, 2016)
Gantry Crane System is a mechanism in heavy engineering that moves payload such as container from one point to another.Generally,an experienced operators or an experts are required to control the gantry position manually while minimizing the payload vibration or swing oscillation. Therefore,those manpower have to be trained in order to operate the gantry crane system safely and efficiently. Thus,in order to overcome this problem,a controller is implemented to the system.This paper presents a controls strategy of Proportional-Integral-Derivative and Variable Structure Control (PID+VSC) in the gantry crane system.The PID controller is used to control the trolley position while the VSC controller is used to control the payload oscillation.The performances are compared to the Proportional-Integral-Derivative and Proportional-Derivative (PID+PD) controller in terms of the precision of trolley position with the minimization of payload oscillation.